Music, Mayhem, and Management: Corporate Improvisation and/as Planning in the Face of a Global Pandemic - Ford, Mike (Critical Studies in Improvisation / Études critiques en improvisation, 2021)
This piece examines the ways in which management consulting firms have co-opted concepts drawn from jazz and improvised music to develop corporate responses to the pandemic.